Minimalisasi Biaya Produksi Sendal Menggunakan Linear Programming: - Indah Haziziyah; Akim M.H. Pardede; Marto Sihombing (VISA: Journal of Vision and Ideas, 2023)
The simplex method is a method used to solve linear programming problems with repeated calculations (iterations) that are performed many times until an optimal solution is reached. In solving linear programming problems, it is necessary to determine the constraints and inequalities contained in linear programming. The simplex method can solve linear programming problems involving many inequalities and many variables. Therefore, the purpose of this research is to optimize the production cost of sandals in the Diona Shoes Home Industry. The steps taken to optimize the production cost of sandals include: observing and collecting data, then making a mathematical model, then optimizing production results using the simplex method (iteration), and finally optimizing production results with the Lindo 16.0 software tool. Keywords: Diona Shoes, Linear Programming, Simplex Method, Lindo 16.0.